YELLOWNESS IS A THREAT TO NEWBORN - A REVIEW - Jena, Manoj; S, Shekhar Mohapatra; Dash, Anshurekha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Jaundice is a very well-known disease found worldwide. Jaundice comes from the French word Jauneâ€ - which means yellow. In medical term, jaundice is known as icterus which is a Greek word. This is a very common disease in the population, which causes the yellowish or greenish pigmentation in the skin and whiteness in the eyes. This is a condition of hyperbilirubinemia in which the amount of bilirubin increases in the blood. In this case, the high amount of bilirubin is found in blood, and the disruption of the movement of bilirubin into the liver and out of the body causes jaundice. Different symptoms seen in this case are yellow skin, yellow/white eyes, dark or reddish urine, loss of appetite, bitter taste of tongue, pale faces, nausea, itching in skin, anfd slow pulse rate. Jaundice may be mild to severe. Different types of jaundice are seen like normal jaundice in newborn, hepatic jaundice, and post-hepatic Jaundice.